Blackstone's guide to the freedom of information act 2000 / by John Wadham,Jonathan Griffiths [and] Kelly Harris - Wadham, John. (Oxford, 2007)
The Blackstone's Guide Series delivers concise and accessible books covering the latest legislative changes and amendments. Published soon after enactment, they offer expert commentary by leading names on the effects, extent and scope of the legislation, plus a full copy of the Act itself. They offer a cost-effective solution to key information needs and are the perfect companion for any practitioner needing to get up to speed with the latest changes. The Freedom of Information Act 2000 created a new statutory 'right to open government'. The Act came into force in January 2005 and has resulted in a large number of requests being made to public authorities. As a result of the number of requests received, there has now also been a number of decision notices issued by the Information Commissioner and the Information Tribunal, which have provided further guidance on the operation of the Act. The 3rd edition of this popular Guide, provides updated commentary and information on developments since the Act came into force in January 2005. It includes discussion of the controversial changes to the fees regime, alongside key decisions and documents from the Information Tribunal, the Information Commissioner and the Department for Constitutional Affairs.
Keywords: Freedom of information act 2000-Great Britian